2017
DOI: 10.1038/s41477-017-0042-4
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of an upstream silencer of FZP increases grain yield in rice

Abstract: Transcriptional silencer and copy number variants (CNVs) are associated with gene expression. However, their roles in generating phenotypes have not been well studied. Here we identified a rice quantitative trait locus, SGDP7 (Small Grain and Dense Panicle 7). SGDP7 is identical to FZP (FRIZZY PANICLE), which represses the formation of axillary meristems. The causal mutation of SGDP7 is an 18-bp fragment, named CNV-18bp, which was inserted ~5.3 kb upstream of FZP and resulted in a tandem duplication in the cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 56 publications
2
107
0
Order By: Relevance
“…Very recently, Bai et al . () indicated that duplication of an 18‐bp fragment about 5.3 kb upstream of FZP found in specific aus accessions could further repress FZP expression and enhance yield, suggesting post‐domestication diversification of FZP .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Bai et al . () indicated that duplication of an 18‐bp fragment about 5.3 kb upstream of FZP found in specific aus accessions could further repress FZP expression and enhance yield, suggesting post‐domestication diversification of FZP .…”
Section: Discussionmentioning
confidence: 99%
“…Either intentionally or fortuitously, ancient humans selected the Del 4-bp , causing decreased FZP expression to increase the number of secondary branches and enhance grain number and yield in domesticated rice, while maintaining normal inflorescence and spikelet formation. Very recently, Bai et al (2017) indicated that duplication of an 18-bp fragment about 5.3 kb upstream of FZP found in specific aus accessions could further repress FZP expression and enhance yield, suggesting post-domestication diversification of FZP.…”
Section: Selection Of Variation In the Cis-regulatory Region Plays Anmentioning
confidence: 99%
“…Overexpression of OsmiR397 led to a greater number of branches and grains per main panicle and substantially enhanced grain yield (Zhang et al, 2013b). Recent research demonstrated that repressed expression FZP could prolong the panicle branching period and increase grain yield (Bai et al, 2017). Huo et al (2017) reported that NUMBER OF GRAINS 1 (NOG1) encoding an enoyl-CoA hydratase can increase the grain yield by enhancing grain number per panicle.…”
Section: Yieldmentioning
confidence: 99%
“…For example, FZP knockout mutants produce extra sequential rounds of branches, but fail to bear grain (Komatsu et al ), and FZP overexpressing plants have a series of defects in spikelet structure, including extra glumes and sterile spikelets (Bai et al ). However, a moderate change in FZP expression, in FZP RNAi plants, and in a germplasm population, produced normal panicles, but with increased grain yield (Bai et al ; Huang et al ).…”
Section: Discussionmentioning
confidence: 99%